Usage of Cryopreserved Placental Tissue When Treating Pregnancy Failure - Grischenko, V. I.; Lazurenko, V. V.; Prokopyuk, O. S.; Aralov, O. N. (Problems of Cryobiology and Cryomedicine, 2003)
The results of cryopreserved placental tissue (CPT) application for keeping pregnancy and when treating its failure resulted from immunological and hormonal shifts in blood of pregnant woman.